Cardiac antibody production to self-antigens in children and adolescents during and following the correction of severe diabetic ketoacidosis. (2nd April 2016) - Hoffman, William H.; Sharma, Monal; Cihakova, Daniela; Talor, Monica V.; Rose, Noel R.; Mohanakumar, T.; Passmore, Gregory G.
Abstract: Diabetic cardiomyopathy (DC) is an independent phenotype of diabetic cardiovascular disease. The understanding of the pathogenesis of DC in young patients with type 1 diabetes (T1D) is limited. The cardiac insults of diabetic ketoacidosis (DKA) and progression of DC could include development of antibodies (Abs) to cardiac self-antigens (SAgs) such as: myosin (M), vimentin (V) and k-alpha 1 tubulin (Kα1T). The goal of this study is to determine if the insults of severe DKA and its inflammatory cascade are associated with immune responses to SAgs. Development of Abs to the SAgs were determined by an ELISA using sera collected at three time points in relation to severe DKA (pH < 7.2). Results demonstrate significant differences between the development of Abs to VIM and a previously reported diastolic abnormality (DA) during DKA and its treatment and a NDA group at 2–3 months post DKA ( p = 0.0452). A significant association is present between T1D duration (<3 years) and Abs to Kα1T ( p = 0.0134). Further, Abs to MYO and VIM are associated with inflammatory cytokines. We propose that severe DKA initiates the synthesis of Abs to cardiac SAgs that are involved in the early immunopathogenesis of DC in young patients with T1D.